Philippines-China relations Geopolitics, economics, and counterterrorism - Banlaoi, Rommel C. editor (Philippine Association for Chinese Studies, Ateneo de Manila University, 2019)
This volume of its Chinese Studies Journal focuses on geopolitics, economics, and counterterrorism – important areas that are currently shaping the direction of Philippines-China relations.